Association Between Gestational Weight Gain and Perinatal Outcomes. Issue 4 (October 2018) - Kominiarek, Michelle A.; Saade, George; Mele, Lisa; Bailit, Jennifer; Reddy, Uma M.; Wapner, Ronald J.; Varner, Michael W.; Thorp, John M.; Caritis, Steve N.; Prasad, Mona; Tita, Alan T.N.; Sorokin, Yoram; et al.
Abstract : OBJECTIVE: To evaluate the association between gestational weight gain and maternal and neonatal outcomes in a large, geographically diverse cohort. METHODS: Trained chart abstractors at 25 hospitals obtained maternal and neonatal data for all deliveries on randomly selected days over 3 years (2008–2011). Gestational weight gain was derived using weight at delivery minus prepregnancy or first-trimester weight and categorized as below, within, or above the Institute of Medicine (IOM) guidelines in this retrospective cohort study. Maternal (primary or repeat cesarean delivery, third- or fourth-degree lacerations, severe postpartum hemorrhage, hypertensive disease of pregnancy) and neonatal (preterm birth, shoulder dystocia, macrosomia, hypoglycemia) outcomes were compared among women in the gestational weight gain categories in unadjusted and adjusted analyses with odds ratios (ORs) and 95% CI reported. Covariates included age, race-ethnicity, tobacco use, insurance type, parity, prior cesarean delivery, pregestational diabetes, hypertension, and hospital type. RESULTS: Of the 29, 861 women included, 51% and 21% had gestational weight gain above and below the guidelines, respectively. There was an association between gestational weight gain above the IOM guidelines and cesarean delivery in both nulliparous women (adjusted OR 1.44, 95% CI 1.31–1.59) and multiparous women (adjusted OR 1.26, 95% CI 1.13–1.41) and hypertensive diseases of pregnancy in nulliparous and multiparous women combined (adjusted OR 1.84, 95% CI 1.66–2.04). For the neonatal outcomes, gestational weight gain above the IOM guidelines was associated with shoulder dystocia (adjusted OR 1.74, 95% CI 1.41–2.14), macrosomia (adjusted OR 2.66, 95% CI 2.03–3.48), and neonatal hypoglycemia (adjusted OR 1.60, 95% CI 1.16–2.22). Gestational weight gain below the guidelines was associated with spontaneous (adjusted OR 1.50, 95% CI 1.31–1.73) and indicated (adjusted OR 1.34, 95% CI 1.12–1.60) preterm birth. CONCLUSION: In a large, diverse cohort with prospectively collected data, gestational weight gain below or above guidelines is associated with a variety of adverse pregnancy outcomes. Abstract : Gestational weight gain below or above the Institute of Medicine guidelines is associated with adverse pregnancy outcomes in a large, geographically diverse cohort.